Hubungan Kemampuan Membaca Pemahaman dengan Menulis Wacana Eksposisi Siswa Kelas X SMAN 5 Padang - Farida, Hendrika Era; Gani, Erizal; Ratna, Ellya (Universitas Negeri Padang, 2012)
The purposes of this studi were (1) to explain the ability of reading comprehension of students of class X 5 SMAN Padang, (2) to explain the ability to write discourse exposition of students of class X 5 SMAN Padang and (3) to analyze the relationship between ability to read understanding and the ability to write discourse exposition students. The methods used in this study is a method of correlation studies. Based on the results of research it was concluded the following points. First, the ability of reading comprehension of students of class X 5 SMAN Padang are on the qualifications is more than enough (68,9). Second, the ability to write an exposition on the qualifications of discourse of students of class X 5 SMAN Padang either (79,58). Third, there are a significant relation exists between ability to read the understanding with the ability to write discourse exposition of students of class X 5 SMAN Padang.